Information and Communication Technology (ICT) and its Impact on Employees’ Performance at Private Management Colleges in the Kathmandu Valley - Gharti, Amit (International Research Journal of MMC, 2022)
This paper aimed to analyze Information and Communication Technology (ICT) and its Impact on employees’ performance at Private Management Colleges in the Kathmandu Valley. This research has reviewed some related literature having similar objectives alongside theoretical framework on the subject matter. This paper adopts the descriptive research design based on secondary data in achieving the stated objective. It has collected the previous literature and analyzed based on the thematic area of the study. Based on the findings, the study recommended that organizations should improve more on its information technology to enhance its productivity. The research results showed that ICT and its availability has a significant positive impact on employee performance.